EXAMINATION OF THE CHEMICAL COMPOSITION OF SPRING WATERS IN AKETI VILLAGE OF LANCHKHUTI MUNICIPALITY - Manuchar Chikovani; Nino Kakhidze; Lali Balavadze; Nino Giorgadze; Monika Pataridze (World Science, 2023)
For the first time the hydrochemical examination of the spring waters of the village of Aketi of Lanchkhuti municipality was conducted. The content of magnesium and calcium ions, hydrocarbonate ions, chloride ions, sulfate ions, dry balance, permanganate oxidation, total iron ions, dissolved oxygen and carbon dioxide is determined. The content of total iron ions, dissolved oxygen and carbon dioxide. Relatively simple and fast chemical and physico-chemical methods with good reproducibility were selected for determination. Biogenic substances were determined by the photometric method. Objective: We aimed to study the chemical composition of the spring waters of Aketi village of Lanchkhuti municipality. We determined the following: the content of magnesium and calcium ions, hydrocarbonate ions, chloride ions, sulfate ions, dry balance, permanganate oxidation, total iron ions, dissolved oxygen and carbon dioxide in the spring waters of Aketi village of Lanchkhuti municipalityThe relevance of the issue lies in the fact that the content of the above-mentioned ions was determined for the first time in the given waters, for which highly sensitive methods were selected.